2018
DOI: 10.1136/archdischild-2018-315366
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes following general anaesthesia in children with hypertrophic cardiomyopathy

Abstract: BackgroundChildren with hypertrophic cardiomyopathy (HCM) have historically been considered to be high-risk candidates for general anaesthesia (GA), but there is currently a paucity of evidence regarding the safety of anaesthesia and perioperative outcomes in this population.MethodsClinical features and outcomes of all paediatric patients (<18 years) with HCM undergoing GA between 2000 and 2016 were reviewed.Results86 patients (median 12.4 years (IQR 6.5, 14.9)) underwent 164 separate GA procedures. Aetiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The combination of hypotension and tachycardia is particularly threatening to subendocardial perfusion. 67,68 Dilated cardiomyopathy is often idiopathic but can be secondary to genetic disorders, infection, drugs, congenital HD, or other medical conditions. Dilated cardiomyopathy is characterized by ventricular dilation, impaired ventricular systolic function, loss of preload recruitable stroke work, and exaggerated depression of stroke volume in the setting of elevated afterload.…”
Section: Cardiomyopathymentioning
confidence: 99%
See 2 more Smart Citations
“…The combination of hypotension and tachycardia is particularly threatening to subendocardial perfusion. 67,68 Dilated cardiomyopathy is often idiopathic but can be secondary to genetic disorders, infection, drugs, congenital HD, or other medical conditions. Dilated cardiomyopathy is characterized by ventricular dilation, impaired ventricular systolic function, loss of preload recruitable stroke work, and exaggerated depression of stroke volume in the setting of elevated afterload.…”
Section: Cardiomyopathymentioning
confidence: 99%
“…The combination of hypotension and tachycardia is particularly threatening to subendocardial perfusion. 67,68…”
Section: Perioperative Considerations For Specific High-risk Cardiac ...mentioning
confidence: 99%
See 1 more Smart Citation
“…7 It is still unknown what specific aspects of HCM may lead to pediatric mortality and complications, but peak LVOT gradients ≥30 mm Hg, intraoperative hypotension, and preexisting ventricular arrhythmias are considered strong identifiers demonstrated in the adult literature. 4 By using a combined spinal-caudal epidural technique, we aimed to minimize wide cardiac physiologic swings that would exacerbate the existing LVOTO. As supported in multiple pediatric studies, neuraxial anesthesia for pediatric patients allows for a stable hemodynamic profile where respiratory status, blood pressure, preload, and oxygen saturations do not change significantly from baseline, with a notable lower incidence of hypotension and need for intervention.…”
Section: Discussionmentioning
confidence: 99%
“…3 A recent study reported a low incidence of adverse events in children with hypertrophic cardiomyopathy (HOCM) undergoing general anesthesia. 4 This demonstrated the importance of expert centers in the management of complex cases. Specifically, the involvement of pediatric cardiac anesthetists in reducing adverse events in children having NCS.…”
Section: Ack N Owled G Em Entsmentioning
confidence: 97%